Козацька ідея у діяльності провідника українського національного руху Івана Луценка на початку ХХ ст. - Музичко, О. (Чорноморська минувшина, 2021)
Метою цієї статті є дослідження діяльності одного з лідерів українського національного руху в Одесі Івана Митрофановича Луценка (1863–1919), що була спрямована на відродження українських козацьких традицій в історичних умовах початку ХХ ст., передусім у процесі Української революції. І. Луценко послідовно прагнув сформувати загони вільного козацтва й у важких умовах зовнішніх та внутрішніх загроз і дещо досяг у цьому напрямі. Цінним є теоретичний публіцистичний доробок І. Луценка присвячений осмисленню феномену історії українського козацтва у порівняльному контексті. The purpose of this article is to study the activities of Ivan Mitrofanovich Lutsenko (1863–1919) about his activities, which were aimed at popularizing the history of the Ukrainian Cossacks, the struggle for the spread of the Cossack worldview and spiritual values. I seek to deepen the study of this issue, based on previous research. The corresponding image of I. Lutsenko was reflected in the first essays-memoirs about him, the authors of which were his friends. G. Zlenko, T. Vintskovsky, V. Lobodaev and others wrote about I. Lutsenko as an adherent of the Cossack idea. I. Lutsenko was born in Poltava region in a family that probably had Cossack roots. In 1908, the first Cossack text by I. Lutsenko was published in the Kyiv newspaper Rada, which had not yet been taken into account by his biographers, including us. The Odessa doctor's note was devoted to the issue of P. Polubotko's treasures, which was relevant in Ukraine in the early twentieth century and then in the 1990s. The thesis about the purpose of these treasures caused doubts in I. Lutsenko, but instead he denied the opinion of D. Yavornytsky that this story is a fabrication. The apogee of the realization of these ideas precisely because of the idea of the revival of the Cossack ethos fell on the period of the Great War and the Ukrainian Revolution of 1917–1921. Many sources and memoirs reflect the contribution of I. Lutsenko during the Ukrainian revolution in the formation of detachments of free Cossacks. I. Lutsenko zealously undertook to implement the decision of the General Cossack Council on the organization of free Cossacks, especially in the regions that still "breathed" the Cossack history and traditions: Katerynoslav, Poltava, Kherson. I. Lutsenko founded and headed the section of free Cossacks at the Odesa Ukrainian Military Council. I. Lutsenko's efforts aimed at forming the neo-Cossack idea and movement were also embodied in his writing of a number of articles on relevant topics, which were published in the Odesa editions of 1917–1918. The basis of the conceptual vision of the doctor of the Ukrainian Cossacks was antiquity and longevity, confidence that historical traditions are the foundation of modernity. He traces the origins of the Cossacks to the times of Russia, the prince's wife and the viche tradition. I. Lutsenko portrayed the social system of the Zaporizhzhya Sich in absolutely ideal tones as the embodiment of the socialist and democratic ideals that humanity dreams of. I. Lutsenko's belief in the success of the revival of the Cossacks was based on his belief in the organic nature of this idea for the Ukrainian people and its immortality. I. Lutsenko considered the hope of external support instead of belief in the strength of his own people to be a tragic historical mistake of Ukrainians. Thus, we can conclude that in general I. Lutsenko's activity was the development of populist traditions of perception of the Cossacks, but in the extreme conditions of the revolution he was one of the few people in the south of Ukraine who modernized this tradition, laid the foundation for the future state vision of the Cossack phenomenon.